1998
DOI: 10.1590/s0103-50531998000600010
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationship of Compounds which are Anti-Schistosomiasis Active

Abstract: O método do orbital molecular AM1 foi empregado para calcular um conjunto de descritores moleculares para vinte neolignanas sintéticas com atividade anti-esquistossomose. O método de reconhecimento de padrão (análise de componentes principais ACP, análise de conglomerados AC e análise de discriminante) foi utilizado para obter a relação entre a estrutura molecular e a atividade biológica. O conjunto de moléculas foi classificado em dois grupos de acordo com seus graus de atividade biológica. Estes resultados p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
(12 reference statements)
0
20
0
Order By: Relevance
“…8 Among many descriptors (variables) that have been utilized in SAR studies, [9][10][11] we have chosen the following descriptors to be evaluated: HOMO -The energy of the highest occupied molecular orbital (eV); LUMO -The energy of the lowest unoccupied molecular orbital (eV); χ -Mulliken's electronegativity (eV); POL -Molecular polarizability (a.u. ); Q N -Net atomic charge on atom N; t -Torsional angle (see Figure 1); d -bond angle (see Figure 1); HE -Hydration energy (kcal mol -1 ); MR -Molecular refractivity (Å 3 ); VOL -Molecular volume (Å 3 ); Log P -Partition coefficient.…”
Section: Calculationsmentioning
confidence: 99%
“…8 Among many descriptors (variables) that have been utilized in SAR studies, [9][10][11] we have chosen the following descriptors to be evaluated: HOMO -The energy of the highest occupied molecular orbital (eV); LUMO -The energy of the lowest unoccupied molecular orbital (eV); χ -Mulliken's electronegativity (eV); POL -Molecular polarizability (a.u. ); Q N -Net atomic charge on atom N; t -Torsional angle (see Figure 1); d -bond angle (see Figure 1); HE -Hydration energy (kcal mol -1 ); MR -Molecular refractivity (Å 3 ); VOL -Molecular volume (Å 3 ); Log P -Partition coefficient.…”
Section: Calculationsmentioning
confidence: 99%
“…From the results obtained with the three chemometric (statistical) methods (PCA, HCA and KNN), we can see that the variables responsible for the separation between active and inactive compounds, i.e. E HOMO , L 14 and L 22 , are all electronic variables. Therefore we can conclude that electronic effects should have an important role when one is trying to understand the activity of neolignan compounds against P. brasiliensis.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation is known as structure-activity relationship (SAR) [18][19][20][21] and many of such studies have been reported in the literature. [22][23][24] The SAR methods have been used with success in pharmaceutical applications, 25 and in this work we calculated the following molecular properties to be correlated with the biological activity under study: log P: the values of this property were obtained from the hydrophobic parameters of the substituents by using the molecular package Spartan 5.0; 26 …”
Section: Quantum Chemical Analysismentioning
confidence: 99%
See 2 more Smart Citations